The Phytochemical constituents and biological activities of sungkai (Peronema canescens Jack) leaves hydroethanolic extracts - Rahayu, Ika; Sudrajat, Susana Elya; Sancnia, Sancnia; Puspasari, Monica; Timotius, Kris Herawan (STKIP Persada Khatulistiwa Sintang, 2024)
Peronema canescens, Jack commonly known as